Indian Christians and The Making of Composite Culture in South India. (November 2018) - Doss, M. Christhu
While North India erupted in rebellion in 1857, South India was experiencing a range of cross-cultural contests between missionary Christianity and local converts, who protested against Indian culture being dismissed as a work of the devil. Converts in the emerging Christian communities, particularly in South India, made efforts to retain their indigenous cultural ethos as part of their lived experience. Early attempts to balance Indian identity with Christian beliefs and practices were later replicated in a second anti-hegemonic movement by claims of Indian Christians for respectful inclusion into the new composite nation of postcolonial India. This article brings out how these two processes of asserting hybridity and equity developed. The initial impact of hegemonising Christianity created a chasm between missionaries and converts, which especially the latter addressed constructively. After 1857, emboldened British hegemonic and missionary activities sparked further divisive identity politics, feeding fresh rebellious ambitions that needed to be pacified to maintain the empire. As more culturally conscious Indian Christians realised that missionary Christianity was antithetical to their lived experiences as part of an emerging Indian nation, they used educational strategies to strengthen the formation of India's composite culture, so that India's Christians could now (re)assert their rightful place within the postcolonial nationalist framework, despite contentions from majoritarian forces.